Natural Compound Mixture, Containing Emodin, Genipin, Chlorogenic Acid, Cimigenoside, and Ginsenoside Rb1, Ameliorates Psoriasis-Like Skin Lesions by Suppressing Inflammation and Proliferation in Keratinocytes. (23rd October 2020) - Nguyen, Uy Thai; Nguyen, Ly Thi Huong; Kim, Bo-Ae; Choi, Min-Jin; Yang, In-Jun; Shin, Heung-Mook
Abstract : Herbal combinations of Rhei Radix et Rhizoma, Gardeniae Fructus, Cimicifugae Rhizoma, and Ginseng Radix have been used in traditional formulas to treat the symptoms of heat and dryness. This study investigated the therapeutic effects of a natural compound mixture (PSM) of these herbal combinations, containing emodin, genipin, chlorogenic acid, cimigenoside, and ginsenoside Rb1, for the treatment of psoriasis and its underlying molecular mechanisms. PSM was applied topically to the dorsal skin lesions of imiquimod- (IMQ-) induced C57BL/6 mice, and the expression of the proinflammatory mediators was investigated. The topical application of 1% PSM reduced psoriasis-like symptoms in IMQ-induced C57BL/6 mice significantly. PSM also attenuated the production of IFN- γ, IL-1 β, and IL-6 in skin lesions. Histological analysis showed that PSM had antipsoriatic effects by reducing the lesional epidermal thickness. Either M5 (IL-1 α, IL-17A, IL-22, oncostatin M, and TNF- α, 10 ng/ml each) or IL-22- (100 ng/ml) stimulated HaCaT cells were used to examine the efficacy and underlying mechanism of PSM. In M5-stimulated HaCaT cells, PSM inhibited the production of C-X-C motif chemokine ligand (CXCL) 10 and C-C motif chemokine ligand (CCL) 20 effectively. Moreover, compared to the use of a single compound, it had synergistic inhibitory effects in CXCL8 production. PSM suppressed the phosphorylation of ERK1/2, p38, and STAT3 signaling pathways in M5-stimulated HaCaT cells. Furthermore, PSM reduced the proliferation rate and K16 and K17 expressions in IL-22-stimulated HaCaT cells by inhibiting the Akt/mTOR signaling pathway. These results suggest that PSM may have a therapeutic potential in the treatment of psoriasis lesions.